Confirmatory factorial analysisof the metacognition scale– Senior - França, Alex Bacadini (2019)
The Metacognition Scale – Senior (EMETA-S) is a Brazilian tool, which seeks to evaluate metacognitive skills focused on metacognitive knowledge and cognitive monitoring in elderly people. This article aims to present a confirmatory factorial analysis of the EMETA-S. To achieve this objective, we performed a confirmatory factorial analysis on a sample of 344 elderly people, aged 60 years or older (M = 68.9 years, SD = 6.9 years), 82% of them were women and 17% were men. The EMETA-S consists of a single factor composed of 34 items with excellent reliability (α = .92). The findings showed that EMETA-S can be considered a promising scale in the evaluation of metacognition for elderly people, once it is a tool that is briefer and easier to apply than the existing instruments in the literature.